2022
DOI: 10.3390/idr14030044
|View full text |Cite
|
Sign up to set email alerts
|

Warm Autoimmune Hemolytic Anemia and Pure Red Cell Aplasia during a Severe COVID-19 B.1.1.7 Infection

Abstract: Warm autoimmune hemolytic anemia (AIHA) is a rare complication of COVID-19 infection. We report a case of warm AIHA in a patient with COVID-19 pneumonia treated with methylprednisolone and several red blood cell transfusions. Despite treatment of the warm AIHA, the patient’s reticulocyte count remained low, and his biochemical markers were suggestive of pure red cell aplasia, which was later attributed to a concurrent parvovirus B19 infection. This case highlights an unusual situation of two separate hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Some cases have been reported as coincidental infections by parvovirus-B19, known to cause PRCA by blocking p-antigens on erythroid precursors, resulting in proliferation and maturation arrest of erythroid precursors [ 18 ]. The case of AIHA and PRCA reported by Ghimire et al [ 14 ] was associated with double infections of COVID-19 and parvovirus-B19, and they suggested that the PRCA in their case was due to parvovirus-B19.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Some cases have been reported as coincidental infections by parvovirus-B19, known to cause PRCA by blocking p-antigens on erythroid precursors, resulting in proliferation and maturation arrest of erythroid precursors [ 18 ]. The case of AIHA and PRCA reported by Ghimire et al [ 14 ] was associated with double infections of COVID-19 and parvovirus-B19, and they suggested that the PRCA in their case was due to parvovirus-B19.…”
Section: Discussionmentioning
confidence: 94%
“…Although previous reports on COVID-19-associated PRCA that were resistant to PSL treatment and recovery after the administration of cyclosporine [ 15 ] or tacrolimus [ 13 ] were published, our case and the case by Karrat et al [ 12 ] showed a good response to PSL as shown in Table 2 . The case by Ghimire et al [ 14 ] also showed a response to dexamethasone. Appropriate selection of the treatment may differ from case to case, depending on the severity of COVID-19 or the host immunologic response of each patient.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations